2015
DOI: 10.1038/srep13779
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits predict brain activation and connectivity when witnessing a violent conflict

Abstract: As observers we excel in decoding the emotional signals telling us that a social interaction is turning violent. The neural substrate and its modulation by personality traits remain ill understood. We performed an fMRI experiment in which participants watched videos displaying a violent conflict between two people. Observers’ attention was directed to either the aggressor or the victim. Focusing on the aggressor (vs. focusing on the victim) activated the superior temporal sulcus (STS), extra-striate body area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…We did find associations however between bilateral STG reactivity to angry faces and aggression on a between-participant basis. STG activity has previously been shown to increase when focusing one’s attention on the aggressor relative to the victim of a violent conflict66, and when appraising unfair proposals as negative67. These findings, in addition to its general involvement in mentalizing62 and threat detection50, suggest that persons with higher reactivity to anger in STG might be more likely to interpret the opponent’s intentions as hostile and hence respond aggressively.…”
Section: Discussionmentioning
confidence: 90%
“…We did find associations however between bilateral STG reactivity to angry faces and aggression on a between-participant basis. STG activity has previously been shown to increase when focusing one’s attention on the aggressor relative to the victim of a violent conflict66, and when appraising unfair proposals as negative67. These findings, in addition to its general involvement in mentalizing62 and threat detection50, suggest that persons with higher reactivity to anger in STG might be more likely to interpret the opponent’s intentions as hostile and hence respond aggressively.…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that FTD patients with the largest atrophy in this network, exhibit the most prominent lack of attention for social cues . Furthermore, activation of the BLA during perception of social emotional expressions is modulated by trait empathy (Van den Stock, Hortensius, et al, 2015), a key deficit in bvFTD.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is hypothesized that amygdalar responses to facial emotion perception influence activation in face-responsive regions like the pSTS and FFA. In addition, there is evidence that the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 modulatory influence on occipito-temporal areas originates primarily in the basolateral section of the amygdala (Bickart, Hollenbeck, Barrett, & Dickerson, 2012;Van den Stock, Hortensius, Sinke, Goebel, & de Gelder, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…We predicted that a common engagement of the mirror and mentalizing systems alongside pSTS underpins the processing of both interaction types (Centelles et al, ; Georgescu et al, ; Iacoboni et al, ; Van den Stock et al, ), while increasing levels of cooperativity and affectivity should reflect in heightened activity of, respectively, mirror and mentalizing areas processing shared behavioral intentions versus shared mental states (Canessa et al, ). We expected such a functional distinction to emerge from effective connectivity within a strongly interconnected network with pSTS as driving input, in which increasing cooperativity and affectivity promote, respectively, the visuomotor processing of motor intentions and the attribution of mental states by key‐nodes of the mirror (vPMC and SPL) and mentalizing (vmPFC) systems.…”
Section: Introductionmentioning
confidence: 99%